Nitrogen Fixation and Plant Growth Enhancement by Beneficial Rhizobacteria in Association with Oil Palm Seedlings - Ahmad Ghazali, Amir Hamzah (2001)
Nitrogen fertilizer is the most expensive nutrient input in oil palm production with average total estimated cost amounting to RM 470 million yea(l. Rapid losses of N fertilizer through leaching further increases the cost on palm oil production and. makes the sector less profitable. Recently there is a new finding about an associated N2 fixing rhizobacteria which could be applied to the oil palm seedling production sector. The beneficial rhizobacteria has been reported to be efficient in N2 fixation and stimulates plant growth, thus could be used as a biofertilizer and bioenhancer, respectively, for various leguminous and non-leguminous crops. Therefore, a series of experiments were carried out to estimate the N2 fixing capacity of the rhizobacteria and to observe the effects of inoculation on growth and development of the associated oil palm seedlings. Results from the initial experiment indicated that Azospirillum could contribute 40% of the total N requirement of oil palm plantlets through N2 fixation process, stimulated total dry matter accumulation and root growth, stimulated uptake and higher concentration of N and K and increased the host photosynthetic rates compared to the control, after 120 days of planting (D120). The subsequent pot experiment (glasshouse experiment, harvested after 130, 260 and 390 days of planting (D130, D260 and D390)) demonstrated the potential of Azospirillum brasilense Sp 7 and locally isolated Bacillus sphaericus UPMB 1 0 and Bacillus subtilis UPMB 13 as a biofertilizer for oil palm seedlings through N2 fixation (25-50% Ndfa